Anglicanism a very short introduction - Chapman, Mark D. (Mark David), 1960- (Oxford : Oxford University Press, 2006)
This short introduction provides an understanding of the diversity of Anglicanism by exploring its history, theology, and structure. It also reveals what it is that holds the Anglican Communion together despite the crises that threaten it.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Church of England; Anglican Communion